Immortal - Shields, Gillian (Katherine Tegen Books, 2010)
Falling in love with the mysterious Sebastian, Evie Johnson, a scholarship student at the Wyldcliffe Abbey School, is haunted by a sisterlike figure that seems to be sending her a warning.